Medical Emergencies in Pulmonary Hypertension - Seitler, Samuel; Dimopoulos, Konstantinos; Ernst, Sabine; Price, Laura C. (Seminars in Respiratory and Critical Care Medicine, 2023)
The management of acute medical emergencies in patients with pulmonary hypertension (PH) can be challenging. Patients with preexisting PH can rapidly deteriorate due to right ventricular decompensation when faced with acute physiological challenges that would usually be considered low-risk scenarios. This review considers the assessment and management of acute medical emergencies in patients with PH, encompassing both pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH), acknowledging these comprise the more severe groups of PH. Management protocols are described in a systems-based approach. Respiratory emergencies include pulmonary embolism, airways disease, and pneumonia; cardiac emergencies including arrhythmia and chest pain with acute myocardial infarction are discussed, alongside PH-specific emergencies such as pulmonary artery dissection and extrinsic coronary artery compression by a dilated proximal pulmonary artery. Other emergencies including sepsis, severe gastroenteritis with dehydration, syncope, and liver failure are also considered. We propose management recommendations for medical emergencies based on available evidence, international guidelines, and expert consensus. We aim to provide advice to the specialist alongside the generalist, and emergency doctors, nurses, and acute physicians in nonspecialist centers. A multidisciplinary team approach is essential in the management of patients with PH, and communication with local and specialist PH centers is paramount. Close hemodynamic monitoring during medical emergencies in patients with preexisting PH is vital, with early referral to critical care recommended given the frequent deterioration and high mortality in this setting.
Keywords: pulmonary hypertension; emergency; pulmonary embolism; arrhythmia; sepsis; hemoptysis